Medical Education in the United States - Torloni, Sérgio; Lassance, Paulo Mauricio Silva; Alves, Mariana Carvalho Medeiros; de Brito, Ana Paula Lottici; Lassance, Fábia Aparecida Carvalho (Revista de Medicina e Saúde de Brasília, 2015)
These authors intend to provide a brief history of the medical educational system in the United States of America (USA), the educational structure, the current topics and challenges facing medical educators. The structure of medical education in the USA differs from most countries. In the USA it is not possible for a student to start medical studies after the completion of high school at the undergraduate level. A student must first complete a four-year undergraduate ’pre-medical’ program at a college or university and obtain a Bachelor’s degree before entering medical school. Upon successful completion of four years of study at medical school, the medical doctor (M.D.) degree is conferred after which physicians take three to seven years of residency training. The whole process can take from 11 to 15 years.